Time to Redefine Organic Agriculture: Can’t GM Crops Be Certified as Organics? - Husaini, Amjad M.; Sohail, Muhammad (Frontiers in Plant Science, 2018)
The challenges of sustainable food production without damaging the environment for a growing human population have increased considerably. The current agricultural practices involving chemical fertilizers and even organic farming are not sustainable in the long run and can have deleterious effects on the environment. Thus, new, innovative solutions need to be identified and propagated for tackling this. Among such innovations, that can complement conventional as well as organic farming methods, are genetic modification (GM) and aquaculture. Yet, GM technologies often face resistance from civil groups owing to an ‘unknown’ fear, akin to Frankenstein’s monster. How real is this fear? Our discussion rests on basic questions like, why can’t ‘organics’ include GM crops that do not require chemical inputs for cultivation, and can GM crops like Golden rice qualify to be ‘organic’ if cultivated through organic practices? Do we need to rethink organic agriculture in the context of the present and future challenges of 21st century?